Antibody-synthesizing lymphocytes (AS-LYMP) and reactive lymphocytes (RE-LYMP): novel predictors of severe dengue - Saputra, I M Yullyantara; Gustawan, I Wayan; Utama, Made Gede Dwilingga; Lestari, AA Wiradewi; Adibrata, Antony Abel; Dewi, Eleonora Anindya Tiara (Indonesian Pediatric Society, 2026)
Background Dengue fever is a major public health problem in Indonesia, where children are particularly at risk of severe disease. Early recognition of severe dengue is critical to reduce morbidity and mortality. Novel lymphocyte activation markers, such as antibody-synthesizing lymphocytes (AS-LYMP) and reactive lymphocytes (RE-LYMP), may improve risk stratification. Objective To evaluate antibody-synthesizing lymphocytes (AS-LYMP) and reactive lymphocytes (RE-LYMP) as potential diagnostic risk stratification markers for severe dengue fever. Methods This cohort retrospective study was conducted at Ngoerah General Hospital, Denpasar, Bali, and included children under 18 years with confirmed dengue infection. AS-LYMP and RE-LYMP counts were obtained using a Sysmex XN-3000 analyzer. Diagnostic performance was evaluated by receiver operating characteristic (ROC) curve analysis, and optimal cut-off points were identified using the Youden index. Results Seventy-nine dengue patients were analyzed: 15 without warning signs, 39 with warning signs, and 25 with severe dengue. Both AS-LYMP and RE-LYMP counts were significantly elevated in severe dengue (P<0.001) compared to other two groups. The ROC analysis showed acceptable accuracy for AS-LYMP (AUC 0.749; cut-off 0.83 × 10³/μL; sensitivity 80.0%; specificity 63.0%) and RE-LYMP (AUC 0.729; cut-off 1.04 × 10³/μL; sensitivity 80.0%; specificity 59.3%). Hemoglobin level and leukocyte count demonstrated predictive value, but with lower accuracy. Conclusion AS-LYMP and RE-LYMP are promising biomarkers for early identification of severe dengue in children. Integration into routine hematology testing may support timely clinical decision-making.